2022
DOI: 10.1111/jce.15648
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences and adherence of patients treated with wearable cardioverter‐defibrillator: Insights from an international multicenter register

Abstract: Aims: Treatment with the wearable cardioverter defibrillator (WCD) may protect against sudden cardiac death (SCD) as a bridging therapy until a cardioverterdefibrillator may be implanted. We analyzed in a multicenter setting a consecutive patient cohort wearing WCD to explore sex differences. Methods and Results:We analyzed 708 consecutive patients, 579 (81.8%) from whom were males and 129 (18.2%) females (age, 60.5 ± 14 vs. 61.6 ± 17 years old; p = .44). While the rate of ischemic cardiomyopathy (ICM) as a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Previously published data to define factors, which are associated with the likelihood of medication non‐adherence among Medicare low‐income subsidy recipients with type 2 diabetes, hypertension or heart failure showed that both young age and male gender are associated with low compliance 11 . Recently published descriptive data showed that the compliance rate regarding wearing a WCD is comparable in males and females 12,13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously published data to define factors, which are associated with the likelihood of medication non‐adherence among Medicare low‐income subsidy recipients with type 2 diabetes, hypertension or heart failure showed that both young age and male gender are associated with low compliance 11 . Recently published descriptive data showed that the compliance rate regarding wearing a WCD is comparable in males and females 12,13 …”
Section: Discussionmentioning
confidence: 99%
“…11 Recently published descriptive data showed that the compliance rate regarding wearing a WCD is comparable in males and females. 12,13 A further important aspect is that NICM is also associated with low compliance. Of note, recently published data suggest that a prolonged period of OMT and a prolonged WCD use in newly diagnosed NICM and ICM is increasing the rate of patients who may not need ICD implantation.…”
Section: Predictors Of Compliancementioning
confidence: 99%
“…The datasets generated during and analysed during the current study are available from the corresponding author on reasonable request. Thomas Kuntz MD 4 Norbert Klein MD 4 Boldizsar Kovacs MD, MSc 5 Firat Duru MD 5 Ardan M. Saguner MD 5 Christian Blockhaus MD 6,7 Dong-In Shin MD 6,7 Michael Gotzmann MD 8 Hendrik Lapp MD 9 Thomas Beiert MD 9 Andreas Mügge MD, PhD 2,10 Ibrahim El-Battrawy MD 2,10 Ibrahim Akin MD, PhD…”
Section: Data Availability Statementmentioning
confidence: 99%
“…3 In our recently published data, we investigated clinical outcome and adherence in a smaller cohort. 4 To analyze gender differences, we investigated in a multicenter−multinational setting (nine centers) a large patient cohort treated with WCD (n = 1596) Table 1.Data from a total of 1596 patients (332 females, 20.8% and 1264 males, 79.2%) regarding indication for wearing WCD, WCD shocks, adherence, and clinical outcome after termination of WCD use at mean follow-up of 20.6 ± 20.3 months were analyzed. Both…”
mentioning
confidence: 99%
See 1 more Smart Citation